2017
DOI: 10.1007/s12041-017-0817-4
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of polymorphisms and selective pressures on ama1 gene in Plasmodium knowlesi isolates from Sabah, Malaysia

Abstract: The apical membrane antigen-1 (AMA-1) of Plasmodium spp. is a merozoite surface antigen that is essential for the recognition and invasion of erythrocytes. Polymorphisms occurring in this surface antigen will cause major obstacles in developing effective malaria vaccines based on AMA-1. The objective of this study was to characterize ama1 gene in Plasmodium knowlesi isolates from Sabah. DNA was extracted from blood samples collected from Keningau, Kota Kinabalu and Kudat. The Pkama1 gene was amplified using ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 38 publications
1
8
0
Order By: Relevance
“…In the present study, the nucleotide diversity and haplotype diversity of Domain I (π: 0.007, Hd: 0.974) are close to the diversity of Domain I (π: 0.008, Hd: 0.941) reported previously for Peninsular Malaysia P. knowlesi isolates (Fong et al, 2015c). The nucleotide diversity of PkAMA-1 from Peninsular Malaysia (π: 0.006) was just slightly higher than that of Sarawak (π: 0.005) (Faber et al, 2015) and Sabah (π: 0.004) (Chua et al, 2017). Thus, it can be generally concluded that genetic polymorphism of PkAMA-1 is low.…”
supporting
confidence: 82%
See 1 more Smart Citation
“…In the present study, the nucleotide diversity and haplotype diversity of Domain I (π: 0.007, Hd: 0.974) are close to the diversity of Domain I (π: 0.008, Hd: 0.941) reported previously for Peninsular Malaysia P. knowlesi isolates (Fong et al, 2015c). The nucleotide diversity of PkAMA-1 from Peninsular Malaysia (π: 0.006) was just slightly higher than that of Sarawak (π: 0.005) (Faber et al, 2015) and Sabah (π: 0.004) (Chua et al, 2017). Thus, it can be generally concluded that genetic polymorphism of PkAMA-1 is low.…”
supporting
confidence: 82%
“…Although AMA-1 is found in all Plasmodium species, but different species show different level of polymorphism of this protein. Studies showed high level of polymorphism in AMA-1 of P. falciparum and P. vivax (Escalante et al, 2001;Rajesh et al, 2007), whereas low level of polymorphism was found in P. knowlesi (Faber et al, 2015;Fong et al, 2015c;Chua et al, 2017).…”
mentioning
confidence: 96%
“…At the same time, the mutations are deleterious to the parasite and the P. knowlesi population is screening for best-adapted variants. 75 Long-term population expansion of P. knowlesi in Malaysia has been suggested to be the cause of this selection. 73 , 79 , 83 There are, however, some differences in natural selection of these proteins in different geographical regions and different parts of the protein.…”
Section: Molecular Epidemiology and Diversitymentioning
confidence: 99%
“… 79 These polymorphisms are probably results of recombination and reproduction cycle of P. knowlesi in multiple hosts. 75 Indeed, the Anopheles vector may exert strong evolutionary pressure on vector-related genes of the parasite, which is an evidence of adaptation of the parasite to the vector distribution or vectorial capacity. 86 …”
Section: Molecular Epidemiology and Diversitymentioning
confidence: 99%
“…Malaysia H 34 Purifying selection 2 clusters were identified Yap et al (2017) [ 143 ] Merozoite surface protein 1 42 kDa region ( msp1 42 ) Erythrocyte invasion Pen. Malaysia, Sabah, Thailand, India H, Macaque 39 Purifying selection within Malaysia isolates Chua et al (2017) [ 144 ] Apical membrane antigen 1 ( ama1 ) Erythrocyte invasion Sabah H 36 Purifying selection De Silva et al (2017) [ 145 ] Merozoite surface protein 1 ( msp3 ) Erythrocyte invasion Pen. Malaysia H 48 Purifying selection in Domain B 2 clusters were identified Ahmed et al (2018) [ 146 ] msp1 Erythrocyte invasion Pen.…”
Section: Introductionmentioning
confidence: 99%